Health tourism trends in the United Kingdom: Are they net exporters of health services? - Pagán-Rodríguez, Ricardo Braulio (My University, 2016)
The study investigates the inbound and outbound health tourism in the United Kingdom (UK) to determine if the UK can be considered as a net exporter of health services. Although there is an increasing number of studies analysing the phenomenon of health tourism, little empirical data are available. This paper contributes to reducing this gap by providing reliable data on health tourism flows for the British case. Using microdata drawn from the International Passenger Survey (IPS) for the period 2000-2014, we estimate the flows, number of nights and expenditure of tourists looking for medical treatment who complete international visits of less than 12 months’ duration to and from the UK. In addition, we analyse the main destinations of UK residents (outbound health tourists), and country of origin of overseas residents (inbound health tourists). The results show the upward trend of inbound and outbound patients (163 and 364% during the period 2000-2014, respectively), the strong seasonality in outbound patients (lower during the summer), and the significant increase in the levels of expenditure of overseas residents since 2005. Poland, France, India and Hungry are the chosen countries by UK residents to be treated, whereas Irish Republic, Spain, United Arab Emirates and Greece are the main countries providing inbound health patients. Public policy considerations are given.
Keywords: Turismo; Health Tourism; Inbound; Outbound; The International Passenger Survey (IPS); United Kingdom